Can water resource tax reform improve the environmental performance of enterprises? evidence from China’s high water-consuming enterprises - Liu, Chenyu (Frontiers in Environmental Science, 2023)
Water scarcity and pollution have become a global problem, especially in China. Whether China can solve the water resources dilemma is closely related to its ability to achieve high-quality development. At present, studies on China's water resources policy are relatively few and all of them are theoretical interpretations or regional studies. There is little literature examining the impact of China's water resources policy on enterprises and its mechanisms. Therefore, this paper takes China's water resource tax reform in 2017 as a quasi-natural event and constructs a difference-in-differences model to investigate the micro-governance effects of water resource tax reform based on panel data of high water-consuming enterprises listed in Shanghai and Shenzhen A-shares between 2012 and 2020. The findings of the study are as follows. Firstly, the water resource tax reform significantly improves the environmental performance of water-intensive enterprises. Secondly, through the mechanism test the author finds that water resource tax reform can promote the research and development of green invention patents in companies, which in turn improves their environmental performance. However, water resource tax showed no significant effect on green utility model patents. Finally, taking into account heterogeneity, this paper points out that the impact of the reform is more prominent in water-scarce regions and among large-scale enterprises. This paper provides experience and evidence for the promotion of water resource tax reform and inspires the author to give some policy recommendations. In the future, China should continue to implement water resource tax policy and increase technical and financial support to enterprises for green innovation.